2013
DOI: 10.1056/nejmoa1212299
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent versus Continuous Androgen Deprivation in Prostate Cancer

Abstract: BACKGROUND Castration resistance occurs in most patients with metastatic hormone-sensitive prostate cancer who are receiving androgen-deprivation therapy. Replacing androgens before progression of the disease is hypothesized to prolong androgen dependence. METHODS Men with newly diagnosed, metastatic, hormone-sensitive prostate cancer, a performance status of 0 to 2, and a prostate-specific antigen (PSA) level of 5 ng per milliliter or higher received a luteinizing hormone–releasing hormone analogue and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
400
3
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 502 publications
(421 citation statements)
references
References 22 publications
6
400
3
12
Order By: Relevance
“…This trial recruited men without evidence of metastatic disease, and patients assigned to intermittent ADT were on therapy only 27% of the time. As expected with earlier stage prostate cancer, median survival was longer (9 years), and prostate cancerspecific mortality (14.2%) lower in this trial 5 compared to the randomized controlled trial in men with metastatic prostate cancer by Hussain et al 4 While the trial by Crook et al 5 showed non-inferiority for overall survival, intermittent therapy was associated with a non-significant increase (9%) of prostate cancer-specific mortality, with a trend towards reduced overall survival in those with a Gleason score of 8-10. Because of the relatively low number of prostate cancer-related deaths, the trial may have been underpowered to show inferiority of intermittent therapy.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…This trial recruited men without evidence of metastatic disease, and patients assigned to intermittent ADT were on therapy only 27% of the time. As expected with earlier stage prostate cancer, median survival was longer (9 years), and prostate cancerspecific mortality (14.2%) lower in this trial 5 compared to the randomized controlled trial in men with metastatic prostate cancer by Hussain et al 4 While the trial by Crook et al 5 showed non-inferiority for overall survival, intermittent therapy was associated with a non-significant increase (9%) of prostate cancer-specific mortality, with a trend towards reduced overall survival in those with a Gleason score of 8-10. Because of the relatively low number of prostate cancer-related deaths, the trial may have been underpowered to show inferiority of intermittent therapy.…”
supporting
confidence: 73%
“…In summary, because the confidence interval limits crossed both unity and the prespecified delta, the findings by Hussain et al 4 were statistically inconclusive. Thus, the results do not imply that intermittent therapy is inferior; rather, the possibility that intermittent therapy is inferior cannot be discounted.…”
mentioning
confidence: 89%
See 3 more Smart Citations